Computational Parallel on Simulation of Wave Attenuation by Mangrove Forest - Gunawan, Putu Harry; Palupi, Irma; Ikhsan, Nurul; Iryanto, Iryanto; Mahmuda, Naila Al (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 14 No 3 (2023): Vol. 14, No. 3 December 2023, 2023)
Coastal ecosystems, specifically mangrove trees, safeguard coastal regions against natural disasters like erosion, floods, and tsunamis. Numerical simulations employing the Shallow Water Equation (SWE), encompassing mass and momentum conservation equations, are used to comprehend how mangroves attenuate wave energy. The SWE incorporates Manning's friction term, which is directly influenced by mangrove forests. However, the SWE's complexity and sensitivity to initial conditions hinder analytical solutions. Despite its increasing computational demands, we utilize the robust staggered grid method to address this challenge. Our study examines mangroves' wave-attenuating effects and introduces a parallel computational model using OpenMP to expedite computations. Findings reveal that mangroves can reduce wave amplitudes by up to 33% when employing a Manning's coefficient of 0.3 within confined basin simulations. Furthermore, our parallel computing experiments demonstrate substantial computation speed enhancements ; the speedup improves up to a point, with a notable 7.26-fold acceleration observed when utilizing eight threads compared to a single line . Moreover, more than a 10-fold acceleration is observed when the number of threads is greater than 16. This underscores the significance of parallelization in exploring mangrove contributions to coastal protection.